Overview of biological mechanisms of human carcinogens. (17th November 2019) - Birkett, Nicholas; Al-Zoughool, Mustafa; Bird, Michael; Baan, Robert A.; Zielinski, Jan; Krewski, Daniel
ABSTRACT: This review summarizes the carcinogenic mechanisms for 109 Group 1 human carcinogens identified as causes of human cancer through Volume 106 of the IARC Monographs. The International Agency for Research on Cancer (IARC) evaluates human, experimental and mechanistic evidence on agents suspected of inducing cancer in humans, using a well-established weight of evidence approach. The monographs provide detailed mechanistic information about all carcinogens. Carcinogens with closely similar mechanisms of action (e.g. agents emitting alpha particles) were combined into groups for the review. A narrative synopsis of the mechanistic profiles for the 86 carcinogens or carcinogen groups is presented, based primarily on information in the IARC monographs, supplemented with a non-systematic review. Most carcinogens included a genotoxic mechanism.